Apremilast Adherence and Persistence in Patients with Psoriasis and Psoriatic Arthritis in the Telehealth Setting Versus the In-person Setting During the COVID-19 Pandemic - Ashis K. Das; Eunice Chang; Caleb Paydar; Michael S. Broder; Kate K. Orroth; Myriam Cordey (Adis, Springer Healthcare, 2023)
Abstract Introduction Limited access to healthcare during the COVID-19 pandemic prompted patients to seek care using telehealth. In this study, we assessed whether treatment patterns differed for patients with psoriasis (PsO) or psoriatic arthritis (PsA) initiating apremilast by either a telehealth or an in-person visit. Methods We estimated adherence and persistence among US patients in the Merative© MarketScan© Commercial and Supplemental Medicare Databases who newly initiated apremilast between April and June 2020, categorized by the type of visit (telehealth or in-person) when apremilast was first prescribed. Adherence was defined as the proportion of days covered (PDC), with PDC ≥ 0.80 considered to indicate high adherence. Persistence was defined as having apremilast available to take without a 60-day gap during follow-up. Factors associated with high adherence and persistence were estimated with logistic and Cox regression. Results Among apremilast initiators (n = 505), the mean age was 47.6 years, 57.8% were female, and the majority had PsO (79.6%). Telehealth index visits were more likely among patients residing in Northeast USA (odds ratio [OR] 3.31, 95% confidence interval [CI] 1.63-6.71) and Western USA (OR 2.52, 95% CI 1.07-5.93]), those with a prescribing rheumatologist (OR 2.27, 95% CI 1.10-4.68), and those with any baseline telehealth visit (OR 1.91, 85% CI 1.20-3.04). Those initiating apremilast with a telehealth visit (n = 141) had similar mean PDC to those initiating apremilast with an in-person visit (n = 364) (0.695 vs. 0.728; p = 0.272). At the end of the 6-month follow-up, 54.3% of the overall population had high adherence (PDC ≥ 0.80) and 65.1% were persistent. After adjusting for potential confounders, patients initiating apremilast via telehealth had similar full adherence (OR 0.80, 95% CI 0.52-1.21) and persistence as those initiating apremilast in-person. Conclusion Patients with PsO and patients with PsA initiating apremilast via telehealth or in-person during the COVID-19 pandemic had similar medication adherence and persistence during the 6-month follow-up period. These data suggest that patients initiating apremilast can be as effectively managed with telehealth visits as with in-person visits.